Early treatment with the von Rosen splint for neonatal instability of the hip is safe regarding avascular necrosis of the femoral head. (3rd March 2016) - Wenger, Daniel; Samuelsson, Hanna; Düppe, Henrik; Tiderius, Carl Johan
Abstract : Background and purpose — Avascular necrosis of the femoral head (AVN) is a complication in treatment of developmental dysplasia of the hip (DDH). We evaluated the risk of AVN after early treatment in the von Rosen splint and measured the diameter of the ossific nucleus at 1 year of age. Children and methods — All children born in Malmö, Sweden, undergo clinical screening for neonatal instability of the hip (NIH). We reviewed 1-year radiographs of all children treated early for NIH in our department from 2003 through 2010. The diameter of the ossific nucleus was measured, and signs of AVN were classified according to Kalamchi-MacEwen. Subsequent radiographs, taken for any reason, were reviewed and a local registry of diagnoses was used to identify subsequent AVN. Results — 229 of 586 children referred because of suspected NIH received early treatment (age ≤ 1 week) for NIH during the study period. 2 of the 229 treated children (0.9%, 95% CI: 0.1–3.1) had grade-1 AVN. Both had spontaneous resolution and were asymptomatic during the observation time (6 and 8 years). 466 children met the inclusion criteria for measurement of the ossific nucleus. Neonatally dislocated hips had significantly smaller ossific nuclei than neonatally stable hips: mean 9.4 mm (95% CI: 9.1–9.8) vs. 11.1 mm (95% CI: 10.9–11.3) at 1 year (p < 0.001). Interpretation — Early treatment with the von Rosen splint for NIH is safe regarding AVN. The ossification of the femoral head is slower in children with NIH than in untreated children with neonatally stable hips.